Pengembangan Instrumen Tes Akurasi dan Heart Rate pada Pukulan Jarak Menengah dalam Olahraga Woodball - Putra, Ismawandi Bripandika; Kusuma, Angga Indra; Utomo , Gatot Margisal (Jurnal Porkes, 2024)
This research has several objectives including developing a valid accuracy and heart rate test in woodball sports, developing a reliable accuracy and heart rate test in woodball sports, norms for the assessment of accuracy and heart rate tests in woodball sports. This research was conducted in six stages of activity, namely identification of needs, product development analysis, writing performance objectives, developing assessment instruments, designing and evaluating products, and revising products. The research trial was conducted at the Master X Woodball Mojokerto club. A total of 37 athletes. To confirm validity, construct validity test was used using inter-items correlations and criterion validity test by connecting data on the accuracy of middle distance shots with the results of 12 fairway games. Tests with test-retest techniques are carried out to test the reliability of test instruments. The final product obtained in this study is to produce an accuracy and heart rate test instrument on middle distance shots that is valid with a validity coefficient of 0.855, reliable with a reliability coefficient of 0.912, and refined with norms for assessing the level of accuracy and heart rate of middle distance shots in playing woodball.